2015
DOI: 10.1371/journal.pone.0142735
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-12 (IL-12)/STAT4 Axis Is an Important Element for β-Cell Dysfunction Induced by Inflammatory Cytokines

Abstract: Pathology driving β-cell loss in diabetes is poorly defined. Chronic subclinical inflammation is associated with β-cell dysfunction. Acute in vitro exposure of islets and β-cells to an inflammatory cytokine cocktail (IL-1β/TNF-α/IFN-γ) results in loss of cell function and viability. The contribution of each cytokine alone or in combination has been evaluated in homogeneous mouse β-cell lines and primary mouse islets. Cytokine cooperation is required for β-cell apoptosis with the most potent combinations includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Generally, the IL-12Rβ2/ JAK2/STAT4 pathway and its activated IFN-gama play a major role in common bioactivities of IL-12, while IL-12Rβ1 was appeared be not found direct function except indispensable subunit responsible for binding IL-12 [36]. But more and more researches indicated that IL-12Rβ1,in single or in aiding IL-12 signalling, vary with cells-type, has many unknown functions [37].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the IL-12Rβ2/ JAK2/STAT4 pathway and its activated IFN-gama play a major role in common bioactivities of IL-12, while IL-12Rβ1 was appeared be not found direct function except indispensable subunit responsible for binding IL-12 [36]. But more and more researches indicated that IL-12Rβ1,in single or in aiding IL-12 signalling, vary with cells-type, has many unknown functions [37].…”
Section: Discussionmentioning
confidence: 99%
“…STAT4 can be activated by IL-12, which is produced by antigen-presenting cells (APCs) and cells that have similar function as APCs; activated STAT4 can promote inflammatory cells like NK cells to produce IFN-γ. 45 Recent studies have suggested that IFN-γ can induce cells to undergo apoptosis through the change of microenvironment 46 and induced autophagy. 47 As an authorized activator of STAT4, IL-12 has the potential to evolve as a hot point in the STAT4-targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The response of islets and β-cells to the inflammatory cytokines weakens the cell viability and function and increases the induction of apoptosis. The IL12/STAT4 axis was found to induce β-cell apoptosis [111]. Serum levels of IFNγ and IL12 are reduced in Stat4 −/− NOD (non-obese diabetic) mice, and the development of diabetes in NOD mice is prevented with the absence of Stat4.…”
Section: T1dmentioning
confidence: 99%